Seni Memahami Doktrin Kenisbian Umur Manusia: Telaah Interpretasi Surah Fatir [35]:11 Perspektif Ibn ‘Ashur - Qurrotul Aini; Nurul Fauziyah; Nabila Nur Kholifatin Nisa; Siti Naila Nahdliyah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to explain the concept of the relativity of human lifespan in order to present a balanced understanding between divine predestination and human effort, while also addressing the assumption of a contradiction between the texts of the Qur’an and the hadith. The study employs a qualitative method with a library research approach and descriptive analysis to explain the findings. The findings indicate that, according to Ibn ‘Ashur, the notion of increase and decrease in lifespan in Surah Fatir verse 11. It shows that such expressions do not indicate any change in Allah’s eternal decree, but rather represents the realization of his will, which always operates in accordance with His knowledge. Human actions such as charity and maintaining family ties are not understood as factors that alter destiny or literally extend lifespan, but instead as signs that Allah has already known and willed the length of a person’s life trought these means. Furtheremore, this article emphasizez that human effort retains its value and significance without negating the certainty of divine knowledge. Inthis way, the study affirms a balanced theological perspective while also opening space for further conceptual discussion on destiny in relation to the realities of contemporary society.